Peran Strategis Kerajaan Mataram Islam dalam Penyebaran Agama Islam dan Ekonomi - Klaudia Marshanda, Klaudia Marshanda Pakpahan; Amelia, Amelia Anggi Bintang; Sarah Clarissa, Sarah Clarissa Hutagalung; Felix Agrian, Felix Agrian Brahmana; Azrina Hendri, Azrina Hendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Islamic Mataram Kingdom is one of the Islamic kingdoms that hasan important role in the spread of Islam on the island of Java. This research examines the spread of Islam during the Islamic Mataram Kingdom as well as its influence in the field of trade in that period and its impact until today. Through a literature study method with a quantitative approach, this research analyzes historical data and trade statistics that show the strategic role of Islamic Mataram in developing regional and international trade networks. The results reveal that the spread of Islam not only impacted religious and cultural aspects, but also strengthened Mataram's economic position through the management of commodity trade such as spices. The influence of trade during the Islamic Mataram period provided a sustainable foundation for the economic and socio-cultural development of the region until today. The findings provide important insights into the relationship between religion, politics and economics in Indonesian history